Adopting machine learning to predict breast cancer patients adherence with lifestyle recommendations and quality of life outcomes - Crispo, Anna; Pagnano, Maria Elisabetta; Bonfigli, Agnese; Pecchia, Leandro; Luongo, Assunta; Porciello, Giuseppe; Coluccia, Sergio; Prete, Melania; Bacco, Luca; Vitale, Sara; Palumbo, Elvira; Giaccone, Paolo; et al. (Frontiers in Digital Health, 2025)
IntroductionHealthy lifestyle behaviors and improved quality of life have been associated with better prognoses in breast cancer survivors. However, sustaining behavioral changes remains challenging; therefore, identifying effective components of lifestyle education programs is essential to enhance adherence, improve quality of life, and facilitate their integration into clinical practice. This study aimed to predict patient adherence to a lifestyle intervention of diet, physical activity, and vitamin D supplementation and to forecast the most frequent Health-Related Quality of Life over the subsequent three measurements.MethodsA total of 316 breast cancer survivors were included in the analysis. Adherence was modeled as a multi-label time series classification task, with compliance recorded on a three-point scale for each treatment component at quarterly intervals over one year. Health-Related Quality of Life was predicted by evaluating first-year adherence data to estimate the mean score over the subsequent three measurements.ResultsThe dataset was split into 70% for training and 30% for evaluation. Random forest classifiers were employed for adherence prediction, achieving accuracy of up to 81%. An XGBoost regressor was used for Health-Related quality of life prediction, and it was compared to a baseline linear regression model. XGBoost demonstrated superior predictive performance, achieving an R-squared value of 0.62.DiscussionOur findings highlight the promise of machine learning techniques in supporting personalized medicine. Advanced predictive models may aid in identifying patients at risk of non-adherence, enabling early interventions, and improving long-term outcomes through tailored lifestyle strategies for breast cancer survivors.